Hubungan Pengetahuan Dan Sikap Remaja Putri Dengan Tindakan Sadari Di SMAN 4 Kabupaten Enrekang - Mutiara Ananda Yusuf; Arman; Sartika (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2025)
Breast self-examination (SADARI) is an efficient and effective way to detect breast cancer early, besides mammography. With SADARI, women can do it independently without spending money to do it, and can increase awareness and vigilance of an abnormal lump in the breast. Therefore, this study aims to investigate the relationship between knowledge, attitudes, peer support, self-motivation, and BSE actions in adolescent girls at SMA Negeri 4, Enrekang Regency, in 2023. This type of research employs quantitative methods, utilizing analytical survey techniques within a cross-sectional study design. The population of this study consisted of 113 adolescent girls in grades X and XI at SMA Negeri 4, Enrekang Regency. The sampling technique employed was a proportional stratified random sampling method, with a sample size of 88 respondents selected using the Slovin formula. The data analysis method employed univariate and bivariate analysis, utilizing the Chi-Square correlation test to display the frequency distribution of all independent variables. From the results of the study, it was found that there was no relationship between knowledge and BSE actions (p = 1.000), there was a relationship between attitudes and BSE actions (p = 0.051), there was a relationship between peer support and BSE actions (p = 0.010), there was a relationship between self-motivation and BSE actions (p = 0.008) in female adolescents in grades X and XI at SMA Negeri 4 Enrekang Regency in 2023. It is hoped that further researchers will build upon the existing research by expanding the variables to be studied using different methods.